HYDRONYM FORMATION IN SARYARKA TOPONYMIC SYSTEM - Bekzatkyzy И. (Hydrometeorology and ecology, 2023)
This article contemplates hydronyms, in particular, one of Kazakhstan’s historical regions – Saryarka. The article examines regularities of toponymic science, its relations with such fields of science as geography, history and linguistics, as well as special characteristics of Saryakra toponymic system. Additionally, it remarks on periods of formation of rivers and lakes, as well as their origins. Special attention is paid to the indicator terms used to designate bodies of water and their role in forming hydrographic names. As a result of the research, it was established that a multitude of regional hydronyms had been formed on the basis of Kazakh language; some of them are related to the ancient language forms. Moreover, the article contains comparative analysis of names of some rivers and lakes from the semantic point of view. Saryarka hydronyms research will allow us to discover more information on the ancient history and geographical features of the region, to learn about the historical ethnographic data on culture, customs, rites and traditions of the peoples from the ancient times. Materials of a field ethnographic expedition have been used in the course of this article’s writing process.